1994
DOI: 10.1111/j.1365-2141.1994.tb06731.x
|View full text |Cite
|
Sign up to set email alerts
|

Intensive chemotherapy with blood progenitor transplantation for primary resistant multiple myeloma

Abstract: This study assessed the feasibility and effect of blood progenitors as the only source of haemopoietic support for myeloablative therapy for patients with primary resistant multiple myeloma and markedly infiltrated bone marrow. 17 patients with advanced, primary resistant myeloma received a priming regimen of cyclophosphamide (3 g/m2) and etoposide (900 mg/m2) with GM-CSF. During haematological recovery, at least 2 x 10(6) CD34+ mononuclear cells/kg were collected from each patient with 4-12 leukaphereses. Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…8,9,15,16 They show that patients with primary refractory disease receiving high-dose therapy fare better than those not undergoing high-dose therapy, 8,9 and that the outcome of patients with refractory relapse treated with high-dose therapy is significantly worse than those with primary refractory disease treated similarly. 15,16 These data have significant practical implications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…8,9,15,16 They show that patients with primary refractory disease receiving high-dose therapy fare better than those not undergoing high-dose therapy, 8,9 and that the outcome of patients with refractory relapse treated with high-dose therapy is significantly worse than those with primary refractory disease treated similarly. 15,16 These data have significant practical implications.…”
Section: Discussionmentioning
confidence: 99%
“…18,20 The response rate of our primary refractory group to high-dose melphalan and autotransplantation is higher than that reported by the MD Anderson group. 8,9 There could be several reasons for this. One is that we proceeded directly to autotransplantation without trying salvage induction regimens or prolonging induction therapy beyond the minimum required to demonstrate lack of response in any given patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dimopoulos et al 29 have published that refractory patients had better outcome after transplantation than after conventional chemotherapy. Terpos et al 20 reported no significant differences in PFS and OS in patients who achieved CR or PR prior to transplantation compared to patients with MR, NR or refractory disease prior to transplantation.…”
Section: Discussionmentioning
confidence: 99%